2017
DOI: 10.1002/jbm.b.34059
|View full text |Cite
|
Sign up to set email alerts
|

Design and properties of a novel radiopaque injectable apatitic calcium phosphate cement, suitable for image‐guided implantation

Abstract: An injectable purely apatitic calcium phosphate cement (CPC) was successfully combined to a water-soluble radiopaque agent (i.e., Xenetix ), to result in an optimized composition that was found to be as satisfactory as poly(methyl methacrylate) (PMMA) formulations used for vertebroplasty, in terms of radiopacity, texture and injectability. For that purpose, the Xenetix dosage in the cement paste was optimized by injection of the radiopaque CPC in human cadaveric vertebrae under classical PMMA vertebroplasty co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…[51][52][53][54] More recently, molecular species have been successfully combined to these commercially available injectable CPCs, to open the way to new indications. This includes for example (i) bupivacaine for the design of a CPC capable to locally deliver an anaesthetic drug for pain release 55 ; (ii) iobitridol, a water-soluble iodinated aromatic contrast agent, for the design of an injectable radiopaque CPC suitable for image-guided implantation 56 . For both formulations, molded blocks of the corresponding CPC were immerged in a 0.9 wt.% sodium chloride solution at 37°C under static conditions, to simulate the release of bupivacaine (resp.…”
Section: Introductionmentioning
confidence: 99%
“…[51][52][53][54] More recently, molecular species have been successfully combined to these commercially available injectable CPCs, to open the way to new indications. This includes for example (i) bupivacaine for the design of a CPC capable to locally deliver an anaesthetic drug for pain release 55 ; (ii) iobitridol, a water-soluble iodinated aromatic contrast agent, for the design of an injectable radiopaque CPC suitable for image-guided implantation 56 . For both formulations, molded blocks of the corresponding CPC were immerged in a 0.9 wt.% sodium chloride solution at 37°C under static conditions, to simulate the release of bupivacaine (resp.…”
Section: Introductionmentioning
confidence: 99%
“…The use of iodine-containing organic compounds as alternative contrast agents has also been explored in bone cements. ,, Iodine-containing organic compounds have the advantage of being covalently bonded to the polymer matrix, resulting in better homogeneity and stability. ,, Multiple studies have investigated 4-IEMA (4-iodobenzoyl-oxo-ethyl methacrylate), a crystalline iodine-containing monomer as an alternative radiopacifier in bone and vertebroplasty cement and found it to be a viable alternative. ,, Le Ferrec et al investigated iobitridol (Xenetix), a contrast agent normally injected into the body for radiographic imaging to enhance the fluoroscopic visibility of a calcium phosphate cement (CPC) for vertebroplasty . This water-soluble contrast was selected in place of BaSO 4 , to prevent the release of insoluble BaSO 4 particles into the bloodstream during resorption of the CPC . Despite its nontoxicity, this contrast agent was rapidly released from the cement, making it unsuitable for long-term monitoring .…”
Section: Resultsmentioning
confidence: 99%
“…It is important that the contrast agents are homogeneously distributed within the polymer matrix, to avoid the presence of agglomerated phases . Some studies suggest the use of nanosized particles that have been chemically functionalized to enable better integration of the two phases. ,, Other studies prefer the use of iodinated nonionic compounds, which can be covalently bonded to the polymer and as a result deter the deterioration of the polymer’s properties and provide better stability of the contrast. , Iodine-containing contrast agents normally consist of iodine molecules attached to an aromatic hydrocarbon group e.g., iodixanol (IDX), iohexol (IHX), iobitridol, and tri-iodobenzoic acid. ,,, When these iodine-containing hydrocarbons are attached to the backbone of the main polymer, the contrast agent becomes a part of the polymer. , The advantage of this covalent bond is that a homogeneous and stable compound is formed and leaching can be minimized …”
Section: Resultsmentioning
confidence: 99%
“…The bupivacaine-loaded cement demonstrated an earlier return to full functional recovery than the ropivacaine-loaded cement, while CPCs retained their mechanical and biological properties. In another study, Le Ferrec et al 222 loaded CPCs with Xenetix® radiopaque agent and reported that incorporating up to 70 mg/mL of Xenetix® into CPCs did not affect the injectability, setting time, and cohesion of the composite. Upon injection in a bone defect in rats, the Xenetix®-loaded CPC appeared to be biocompatible.…”
Section: Drug-loaded Bone Cementsmentioning
confidence: 99%
“…Upon injection in a bone defect in rats, the Xenetix®-loaded CPC appeared to be biocompatible. 222 A recent review paper by Parent et al 223 has elaborated on the design of CPCs for drug delivery applications, with an emphasis on the parameters affecting the loading and release of therapeutic substances. In addition, a paper by Ginebra et al 90 provides an overview of drug release from CPCs for low molecular weight drugs (e.g., antibiotics, non-steroidal anti-inflammatories, anti-cancer drugs, and anti-osteoporotics) and for high molecular weight molecules (e.g., growth factors and other proteins).…”
Section: Drug-loaded Bone Cementsmentioning
confidence: 99%